Markov model of option pricing - Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2021)
In the article is proposed the algorithm of modeling the dynamics of asset prices by Markov process with continuous time and countable set of states and numerical option pricing.
Keywords: assets dynamics; mixture of exponential distributions; Markov model of asset prices; numerical option pricing